Resistance mechanisms involved in complex immunity of wheat against rust diseases - E. S. Skolotneva; E. A. Salina (Вавиловский журнал генетики и селекции)
The review is devoted to the disclosure of the modern concept of plant immunity as a hierarchical system of plant host protection, controlled by combinations of major and minor resistance genes (loci). The “zigzag” model is described in detail for discussing the molecular bases of plant immunity with key concepts: pathogen-associated molecular patterns triggering innate immunity, ambivalent effectors causing susceptibility, but when interacting with resistance genes, a hypersensitive reaction or alternative defense mechanisms. There are three types of resistance in cereals: (1) basal resistance provided by plasma membrane-localized receptors proteins; (2) racespecific resistance provided by intracellular immune R-receptors; (3) partial resistance conferred by quantitative gene loci. The system ‘wheat (Triticum aestivum) – the fungus causing leaf rust (Puccinia triticina)’ is an interesting model for observing all the resistance mechanisms listed above, since the strategy of this pathogen is aimed at the constitutive use of host resources. The review focuses on known wheat genes responsible for various types of resistance to leaf rust: race-specific genes Lr1, Lr10, Lr19, and Lr21; adult resistance genes which are hypersensitive Lr12, Lr13, Lr22a, Lr22b, Lr35, Lr48, and Lr49; nonhypersensitive genes conferring partial resistance Lr34, Lr46, Lr67, and Lr77. The involvement of some wheat R-genes in pre-haustorial resistance to leaf rust has been discovered recently: Lr1, Lr3a, Lr9, LrB, Lr19, Lr21, Lr38. The presence of these genes in the genotype ensures the interruption of early pathogenesis through the following mechanisms: disorientation and branching of the germ tube; formation of aberrant fungal penetration structures (appressorium, substomatal vesicle); accumulation of callose in mesophyll cell walls. Breeding for immunity is accelerated by implementation of data on various mechanisms of wheat resistance to rust diseases, which are summarized in this review.